On Multiverses (or Parallel Universes) of Matrix Triple Solutions of the Diophantine Equation X3 + Y 6 = Z (London Journal of Research In Science: Natural and Formal, 2024)
We show that the Diophantine equation X 3 + Y 6 = Z 6 (0.1) admits matrix triple solutions from M3(N) and M6k(N), k ? N. We construct infinite universes made of these solutions. We introduce different construction structures sets of matrix solutions associated to the Diophantine equation (0.1). These construction structures sets of matrix solutions allow us to show that there exists an infinite number of multiverses (parallel universes) of the matrix solutions of the Diophantine equation (0.1) containing each a finite number of universes of matrix triples.
Keywords: small-sized sprayer; sprayer; spray angle; field boom; transverse vibrations; spray uniformity; nomogram.; Regeneration rainforest; Environmental services; Species richness; Biodiversity; and Tropical rainforest.; X-ray diffraction; Discrete Wavelet Transform; GhostNetV2; BNN; FNN; KOA.; Diophantine Equations; Matrices of integers